Effects of the prebiotic mannan oligosaccharide on the experimental periodontitis in rats. (20th August 2018) - Levi, Yara L. A. S.; Novais, Gabriela S.; Dias, Raisa B.; Andraus, Rodrigo A. C.; Messora, Michel R.; Neto, Hermann B.; Ervolino, Edilson; Santinoni, Carolina S.; Maia, Luciana P.
Abstract: Aim: To evaluate the effect of the prebiotic (PREB) mannan oligosaccharide (MOS) on the progression of the experimental periodontitis (EP) and intestinal morphology in rats. Materials and Methods: Forty rats were randomly allocated into groups ( n = 10): C (control), PREB, EP and EP‐PREB. Groups PREB and EP‐PREB received MOS incorporated into the feed daily. After 30 days, groups EP and EP‐PREB received a cotton ligature around their mandibular first molars, kept for 14 days. Morphometrical, histomorphometrical, microcomputed tomography, gene expression analyses and immunohistochemistry were performed. Data were statistically analysed ( p < 0.05). Results: Group EP‐PREB showed less interproximal bone loss, area without bone in the furcation and bone porosity, and greater bone mineral density than group EP ( p < 0.05). It was also observed a significant decrease in IL‐10 and IFN‐γ gene expression, besides a decrease in TNF‐α and IL‐1β and an increase in TGF‐β immunolabeling score for group EP‐PREB. Group EP‐PREB also presented villous height and crept depth values similar to group C, while group EP presented reduced values ( p < 0.05). Conclusion: It can be concluded that the oral administration of MOS promotes a protective effect against alveolar bone loss caused by EP in rats, modifying histologic and immune‐inflammatory parameters, in addition to protecting the intestine.